2022
DOI: 10.2174/2210315510999200914153725
|View full text |Cite
|
Sign up to set email alerts
|

Anastatica hierochuntica Extracts: Promising, Safe and Selective Anticancer Agents

Abstract: Background: Medicinal plants have been used for many centuries for their significant phytochemical reservoir, forming a foundation for many medicinal drugs. Conventional cancer therapy possesses a number of undesired problems including poor selectivity, severe side effects and resistance of cancer. Objective: There is a need for new anticancer drugs possibly from natural sources such as medicinal plants. A. Hierochuntica L. is rich with phytochemicals and is widely used in traditional medicine. Method: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Further, Table 2 illustrates several identified compounds with reported potency as anti-inflammatory and antioxidant [39], cytotoxic [40], antimicrobial [42] and anti-helminthic [43] agents. and antitumor effects [56]. Our results revealed that the crude extract was rich in glucosidic flavonoids (luteolin and apigenin), possessing structures that exhibit C2=C3 double bonds-see Figure 10-which were previously reported for their anticancer potential [40] and are in agreement with earlier information regarding the impact of flavonoids and other antioxidants [39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, Table 2 illustrates several identified compounds with reported potency as anti-inflammatory and antioxidant [39], cytotoxic [40], antimicrobial [42] and anti-helminthic [43] agents. and antitumor effects [56]. Our results revealed that the crude extract was rich in glucosidic flavonoids (luteolin and apigenin), possessing structures that exhibit C2=C3 double bonds-see Figure 10-which were previously reported for their anticancer potential [40] and are in agreement with earlier information regarding the impact of flavonoids and other antioxidants [39].…”
Section: Discussionsupporting
confidence: 91%
“…In the treatment of cancers such as AML, resistance to cytotoxic chemotherapy becomes a major obstacle [55]. The natural extracts of A. hierochuntica have great antioxidant and antitumor effects [56]. Our results revealed that the crude extract was rich in glucosidic flavonoids (luteolin and apigenin), possessing structures that exhibit C2=C3 double bonds-see Figure 10-which were previously reported for their anticancer potential [40] and are in agreement with earlier information regarding the impact of flavonoids and other antioxidants [39].…”
Section: Discussionmentioning
confidence: 99%
“…Efati et al [35] reported that L. sativum showed IC50 value of 17.8 μg/mL against SW480, HT-29 and Caco-2 colorectal cancer cell lines, also the cytotoxic activity of seed extracts of L. sativum was tested against human neuroblastoma (IMR-32), colon cancer (HT-15 and 29), and lung cancer (A-549) cell lines [28]. Al-Eisawi, et al, [36] observed the antitumor activity of all tested concentrations of A. hierochuntica against leukemia (K-562) and melanoma (A-375) cells. The antitumor activity of tested plants may be due to the presence of phytochemicals content in extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive array of bioactive chemicals found within this particular subject matter offers promising prospects for precise and focused interventions. The potential for enhanced cancer management lies in the utilization of the synergistic effects between natural medicines and conventional therapy (Al-Eisawi et al, 2022a;Al-Eisawi et al, 2022b;Eldesouki et al, 2022;Bou Malhab et al, 2023;Tarawneh et al, 2023).…”
Section: Natural Productmentioning
confidence: 99%